Contemporary psychological problems of students of the College of Basic Education And its relationship to some variables - lect. Khoshi Latif Taha; Asst. Prof. Dr. Wafaa Mohammed Hussein Ahmed (Journal of College of Education, 2025)
Psychological problems have a negative impact on various aspects of daily life.The study aims to determine the level of psychological problems among students in this college. Additionally, it examines whether there are differences in psychological problems based on certain variables, such as students’ specialties (Humanities versus Sciences), gender (male and female), and academic stage (second and fourth years). Two hundred and twenty-nine students from eight different departments within the College of Basic Education participated in the current study. To measure psychological problems a questionnaire was prepared by the researchers after assessing various psychometric properties, including validity and reliability. A satisfactory Cronbach’s alpha of 0.76 and a split-half reliability coefficient of 0.72 were obtained respectively. The normality of the data was assessed using the Kolmogorov-Smirnov test, which indicated no significant deviations from normality (p-value for the Kolmogorov test > 0.05). Descriptive statistics (means and standard deviations), one-sample t-tests, and independent sample t-tests were utilized for data analysis. The findings revealed that students in the College of Basic Education exhibited a low level of psychological problems. Notably, there were no statistically significant differences in psychological problems based on students’ specialties and gender. However, a statistically significant difference was found based on academic stage, suggesting that students in the fourth-year experience more psychological problems than those in the second year. In the light of these findings, several recommendations and suggestions were highlighted.